MORPHOLOGY AND AGE-RELATED, REGIONAL FEATURES OF MORPHOMETRIC INDICATORS OF LYMPHOID STRUCTURES OF HUMAN INTRAHEPATIC DUCTS IN NORM - Aliyeva, N.H.; Huseynov, B.M. (World of Medicine and Biology, 2025)
The lack of reliable information on the morphology of the lymphoid structures of the intrahepatic bile ducts complicates the diagnosis and treatment of various liver pathologies associated with these structures. Therefore, intrahepatic bile ducts taken from 48 corpses of different ages were examined using microscopic and morphometric methods. The studies showed that intraepithelial lymphocytes are found in the walls of the intrahepatic ducts. In the right and left hepatic ducts, diffuse lymphoid tissue is additionally determined. The density of intraepithelial lymphocytes and diffuse lymphoid tissue cells of the intrahepatic bile ducts reaches a maximum in early childhood, and these indicators decrease at later ages. In all age groups, the density of intraepithelial lymphocytes increases from the interlobular duct to the right and left hepatic ducts. Except for newborns, at other ages, the density of diffuse lymphoid tissue cells in the right hepatic duct is higher than in the left.